Pharmacopuncture for Cervicogenic Dizziness - Yunna Kim; Seung-Hun Cho (Korean Pharmacopuncture Institute, 2018)
Objectives: Pharmacopuncture is a treatment that medicinal fluid including herbal extract is injected in body under qi/flavor theory and meridian theories. There are a number of studies investigating the efficacy of pharmacopuncture for cervicogenic dizziness but its usage differs in each study. This study aimed to review previous studies of pharmacopuncture treatment for cervicogenic dizziness to navigate the direction of improvement. Methods: Literature review was conducted on studies aimed at pharmacopuncture for cervicogenic dizziness. The randomized controlled studies which assessed the efficacy of pharmacopuncture on cervicogenic dizziness were selected. The studies were searched in Pubmed, RISS, OASIS and CNKI. After selecting eligible studies, the authors read the articles and summarized the points those are necessary in pharmacopuncture treatment for cervicogenic dizziness. Results: Twenty seven studies and 2,709 participants were included. The diverse solutions were used and the most popular were Salvia miltiorrhiza, Angelica gigas, a compound in Gastrodia elata, Panax notoginseng saponins. Some studies investigated the efficacy of conventional medical compounds (lidocaine, vitamin B, dexamethasone) injected in acupoints. Adopting acupoints and combining with body acupuncture have shown the tendency to enhance the cure rate. Pharmacopuncture could improve the efficacy of conventional treatment for cervicogenic dizziness. Conclusion: As the solution and injection method varies, principles of pharmacopuncture for dizziness should be investigated.